Slat Noise from an MD30P30N Airfoil at Extreme Angles of Attack - Amaral, Filipe Ramos do; Tadashi Himeno, Fernando Henrique; Pagani, Carlos do Carmo [UNESP]; Faraco de Medeiros, Marcello Augusto (Amer Inst Aeronautics Astronautics, 2018)
This study investigates the slat noise of a two-dimensional scaled, unswept, and untapered MD30P30N high-lift model. The experimental data refer to aeroacoustic and aerodynamic measurements in a closed-section wind tunnel for a wide range of angles of attack (from -6 deg up to the stall; approximately at 18 deg) and Mach numbers between 0.07 and 0.1. Three slat configurations (the original MD30P30N, another with a higher slat deflection, and one with smaller slat gap and overlap) are studied experimentally. The signal processing applied to the acoustic data involves conventional beamforming enhanced by two deconvolution algorithms, namely, DAMAS and CLEAN-SC. An original variation of the beamforming cluster approach that is based on the coherence level among microphone pairs is introduced, and it improves the results obtained by DAMAS. Below -2 deg and above 12 deg angles of attack, the slat noise is very small and mostly below the wind-tunnel background noise for all configurations. Between -2 and 12 deg angles of attack, the slat noise spectra are substantially affected by the slat configuration, although it always contains a dominant low-frequency content, a midfrequency broadband noise, and a single high-frequency broad peak. Within this range, the lower angles of attack display the strongest low-frequency narrowband peaks. In fact, at lower angles of attack, the low-frequency narrowband peaks scale with a Mach power above 10.